Fourth Semester Students’ Reading Comprehension Ability in Narrative Text Using Online Sources of FKIP Unilak - Herdi Herdi (Universitas Lancang Kuning, 2020)
Reading comprehension can be done using online sources such as internet, Narrative text can be easily obtained by students on various internet sites in the form of links that are already available. The purpose of this study was to determine the reading comprehension ability of fourth semester students of English Education Department of Universitas Lancang Kuning in narrative texts. This research is descriptive quantitative using online sources. This study used total sampling technique with 70 students who are divided into 3 classes in the English Education Department. Based on results of data analysis, it was found that the students of English Education Department had medium (10.00) ability to comprehend narrative texts. This is indicated by the fact that 24 (34.3%) of students have medium ability to comprehend narrative texts. 29 (41.4%) of students had low ability in scanning the text and mentioning the orientation. 29 (41.4%) of students had low ability in mentioning the complication of the text. 25 (35.7%) of students had low ability in determining and mentioning resolution of the text. 38 (54.3%) of students had medium ability in skimming and determining generic structure, language features, social functions of the text. So, it can be concluded that the fourth semester students’ reading comprehension ability in narrative texts was in medium category with the percentage 54.3%.